The Role of Pragmatics in Improving English Listening and Speaking Skills - Dea Saharani; Siregar, Huda Hizkia Ahmad; Hasibuan, Syafira Hasan; Dalimunthe, Alya Fadhillah; Siregar, Deasy Yunita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
Pragmatics is the study of how we make sense of what others say when we talk. Meaning links our words with our body language. It can change depending on the circumstance, the relationship between the individuals, and other social variables. Its quick growth has made English a worldwide language that brings people together. English is a language that many people from different places and cultures can speak. In everyday life, people use English in many different situations and talk in many different ways. Speakers need to know about different aspects of pragmatics to avoid misunderstandings when they talk and listen. Using English in fun and interesting ways can help everyone, especially those learning it as a second language, get better at talking and writing. Thomas describes "down to soil competence" as the ability to think carefully about what words mean.. It seems like you just shared a number (524) without any extra information or instructions. Please show me the text you want me to make easier to understand. Being good at business means you can talk clearly and choose the right words for different people and situations. The main goal for anyone teaching English to people who don’t speak it as their first language is to help them get better at it, which can be difficult. Keywords: Pragmatics Listening and speaking English